Horizontal MicroRNA Transfer by Platelets – Evidence and Implications - Mussbacher, Marion; Pirabe, Anita; Brunnthaler, Laura; Schrottmaier, Waltraud C.; Assinger, Alice (Frontiers in Physiology, 2021)
For decades, platelets have been known for their central role in hemostasis and their ability to release bioactive molecules, allowing inter-platelet communication and crosstalk with the immune system and vascular cells. However, with the detection of microRNAs in platelets and platelet-derived microvesicles, a new level of inter-cellular regulation was revealed. By shedding microvesicles from their plasma membrane, platelets are able to release functional microRNA complexes that are protected from plasma RNases. Upon contact with macrophages, endothelial cells and smooth muscle cells platelet microRNAs are rapidly internalized and fine-tune the functionality of the recipient cell by post-transcriptional reprogramming. Moreover, microRNA transfer by platelet microvesicles allows infiltration into tissues with limited cellular access such as solid tumors, thereby they not only modulate tumor progression but also provide a potential route for drug delivery. Understanding the precise mechanisms of horizontal transfer of platelet microRNAs under physiological and pathological conditions allows to design side-specific therapeutic (micro)RNA delivery systems. This review summarizes the current knowledge and the scientific evidence of horizontal microRNA transfer by platelets and platelet-derived microvesicles into vascular and non-vascular cells and its physiological consequences.